Education Financing as an Effort to Improve The Quality of Education - Meilina Mira Sari (Universitas Negeri Semarang, 2023)
Based on the discussion, it can be concluded that education costs have an important influence on improving the quality of education. It is hoped that the use of education costs evenly will be able to improve the quality and quality of education as a whole in all levels of society. There is a need for cooperation between the government, regional government and the community to support a high-quality and high-quality learning process. Quality and high quality education will be accompanied by high educational costs. The higher the quality of education, the higher the cost of education, and the lower the quality of education, the lower the cost of education. This article was prepared using qualitative research techniques, in particular a literature review. Some of the key references used in writing this article are scientific journals, books, and previous research on the topic of interest. Education costs have a significant relationship in efforts to improve the quality of education in schools. Without funds, the quality of education will not be in accordance with educational goals. By using various funding sources, schools are expected to be able to improve the quality of education in accordance with the goals they want to achieve. Based on the discussion, it can be concluded that education costs have an important influence on improving the quality of education. It is hoped that the use of education costs evenly will be able to improve the quality and quality of education as a whole in all levels of society. There is a need for cooperation between the government, regional government and the community to support a high-quality and high-quality learning process. Quality and high quality education will be accompanied by high educational costs. The higher the quality of education, the higher the cost of education, and the lower the quality of education, the lower the cost of education.